Osteoradionecrosis of the jaw: comparison between bone and soft tissue injury and their influence on surgical outcomes : a retrospective cohort study - Ristow, Oliver; Birgel, Jan Lukas; Rückschloß, Thomas; Held, Thomas; Uzun-Lang, Kristin; Smielowski, Maximilian; Zittel, Sven; Moratin, Julius; Pilz, Maximilian; Engel, Michael; Hoffmann, Jürgen; Semmelmayer, Karl (Diagnostics, 2023)
Surgical therapy of osteoradionecrosis of the jaw (ORN) is challenging and requires treatment of the affected hard and soft tissue. To understand how tissue injury after irradiation influences surgical outcomes, the objective of this study was to find out whether (a) bone-related, (b) soft tissue-related, and (c) treatment-related parameters influence the surgical success of patients with ORN. A total of 175 patients (324 lesions) were included in this retrospective, single-center study. All patients were diagnosed with ORN and underwent surgical therapy. The primary outcome was complete soft tissue recovery (mucosa/skin) and the absence of symptoms 3 months after surgery. At the time of follow-up, 58% of patients (189 of 324 lesions) had intact intraoral or extraoral soft tissue. The extent of bone destruction had no effect on treatment success, whereas soft tissue injury due to fibrosis (OR: 0.344; CI 0.142-0.834; p = 0.01818) and xerostomia (OR: 0.163; CI 0.064-0.419; p = 0.00016) increased the probability of treatment failure. Soft tissue reconstruction with a microvascular graft improved therapeutic success compared to local wound closure (OR: 2.998; CI 1.371-6.555; p = 0.006). Thus, for the treatment of ORN, it is extremely important to pay attention not only to the extent of bone destruction but especially to soft tissue defects. Because the extent of soft tissue injury is a predictor for therapeutic success, it should influence the choice of surgical treatment.